2014
DOI: 10.1371/journal.pone.0096733
|View full text |Cite|
|
Sign up to set email alerts
|

BNIP3 Regulates AT101 [(-)-Gossypol] Induced Death in Malignant Peripheral Nerve Sheath Tumor Cells

Abstract: Malignant peripheral nerve sheath tumors (MPNSTs) are aggressive Schwann cell-derived sarcomas and are the leading cause of mortality in patients with neurofibromatosis type 1 (NF1). Current treatment modalities have been largely ineffective, resulting in a high rate of MPNST recurrence and poor five-year patient survival. This necessitates the exploration of alternative chemotherapeutic options for MPNST patients. This study sought to assess the cytotoxic effect of the BH3-mimetic AT101 [(-)-gossypol] on MPNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…The mRNA levels of BNIP3 and BNIP3L were strongly upregulated upon treatment with AT 101 in U87MG, MZ-54 and U343 cells ( Figure 6(a,b)). These data are consistent with another study showing upregulation of BNIP3 upon AT 101 treatment [39]. We also investigated the expression of the selective cargo receptor SQSTM1/p62 (sequestome 1), which has been described to participate in the PINK1-PRKN mitophagy pathway [33].…”
Section: Effects Of Bnip3 and Bnip3l Depletion On Mitophagy And Cell supporting
confidence: 89%
“…The mRNA levels of BNIP3 and BNIP3L were strongly upregulated upon treatment with AT 101 in U87MG, MZ-54 and U343 cells ( Figure 6(a,b)). These data are consistent with another study showing upregulation of BNIP3 upon AT 101 treatment [39]. We also investigated the expression of the selective cargo receptor SQSTM1/p62 (sequestome 1), which has been described to participate in the PINK1-PRKN mitophagy pathway [33].…”
Section: Effects Of Bnip3 and Bnip3l Depletion On Mitophagy And Cell supporting
confidence: 89%
“…In the present study, (-)-gossypol nanoparticles were shown to effectively inhibit the growth of prostate cancer PC-3 cells in vitro , with their toxicity similar to that of free (-)-gossypol. In a previous study ( 18 ), the slow-release ability of (-)-gossypol was revealed, with a potential release of ~40% in 48 h. At the same dose, (-)-gossypol nanoparticles release less compared with free (-)-gossypol, indicating that the antitumor effect of (-)-gossypol nanoparticles is stronger than that of free (-)-gossypol. This may result from the ability of nanoparticles to penetrate into cells through cell endocytosis, which is not possible for small-molecule drugs ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 90%
“…It was previously established that Hif-1α is a transcriptional regulator of Bnip3 [ 26 ]. Recently, AT-101 (modified enantiomer of gossypol) was shown to stabilize Hif-1α protein without any increase in mRNA levels [ 27 ]. Furthermore, under normoxic conditions Hif-1α is spontaneously hydroxylated by prolyl hydroxylase, an enzyme that requires oxygen and iron to perform its enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, under normoxic conditions Hif-1α is spontaneously hydroxylated by prolyl hydroxylase, an enzyme that requires oxygen and iron to perform its enzymatic activity. AT-101 treatment caused intracellular iron chelation and resulted in accumulation of Hif-1α in nerve sheath tumor cells [ 27 ]. In our study, Sabutoclax-induced Hif-1α, Bnip3 and LC3-II and expression was blocked significantly when the media was supplemented with iron in the form of ferric citrate ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%